Synergistic effect of PCPE1 and sFRP2 on the processing of procollagens via BMP1. Issue 1 (23rd November 2018) - Zhu, Qin; Guo, Wei; Zhang, Shengjie; Feng, Yang; Wang, Xiao; Zhou, Libin; Huang, Guo‐Ru
Abstract : Procollagen processing is essential for organ development and tissue functions. Both procollagen C‐proteinase enhancer 1 (PCPE1) and secreted frizzled‐related protein 2 (sFRP2) play vital roles in collagen formation via regulating the procollagen C‐proteinase activity of bone morphogenetic protein 1 (BMP1). However, whether the two proteins exert a synergistic effect on BMP1 activity remains unclear. Here, simultaneous knockdown of sFRP2 and PCPE1 led to less collagen formation in mouse embryonic fibroblasts and dorsalized phenotypes in zebrafish embryos. Further studies revealed a direct interaction between the Frizzled domain of sFRP2 and the complement/Uegf/BMP‐1 domain of PCPE1, which enhances the cleavage activity of BMP1 on procollagen. These results suggest that double silencing of sFRP2 and PCPE1 may provide a strategy for treating fibrosis diseases caused by collagen deposition. Abstract :